2007
DOI: 10.1192/pb.bp.106.012310
|View full text |Cite
|
Sign up to set email alerts
|

‘Why did I become a psychiatrist?’: survey of consultant psychiatrists

Abstract: Aims and MethodTo find out why consultant psychiatrists chose psychiatry as a career. A questionnaire was developed and posted to 87 consultant psychiatrists in substantive posts within a London psychiatric training scheme.ResultsThe survey had a response rate of 83% (72 out of 87). The majority of consultants (n=40) chose psychiatry as a career after leaving medical school. The most important reasons cited were empathy with the patient group (36.1%), the interface of psychiatry with the neurosciences (25%), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…There are inconsistent results in the literature on the timing of the selection of psychiatry as a specialty [2,4,8]. Many studies emphasized that the choice of psychiatry as a career was made before entering medical school [4], while other studies underlined the importance of psychiatric teaching and the psychiatry clerkship experience [2,9,10]. In the study of Dein et al [8], the majority of 87 consultant psychiatrists indicated that they made the decision to specialize in psychiatry after medical school.…”
Section: Discussionmentioning
confidence: 99%
“…There are inconsistent results in the literature on the timing of the selection of psychiatry as a specialty [2,4,8]. Many studies emphasized that the choice of psychiatry as a career was made before entering medical school [4], while other studies underlined the importance of psychiatric teaching and the psychiatry clerkship experience [2,9,10]. In the study of Dein et al [8], the majority of 87 consultant psychiatrists indicated that they made the decision to specialize in psychiatry after medical school.…”
Section: Discussionmentioning
confidence: 99%
“…14 A key potential influence on medical student interest in psychiatry is the clinical attachment. 11,15,16 Several reviews have briefly addressed this area, 11,15,17,18 but they lack a systematic methodology. They suggest that the clinical attachment is an important factor in recruitment to psychiatry and that it may positively affect attitudes to psychiatry, but that this may be transient.…”
mentioning
confidence: 99%
“…Previous research has shown that, although an interest in and aptitude for psychiatry are important factors in making doctors take up psychiatry (Goldacre et al 2005), students can be put off by negative attitudes of senior clinicians and poor placement experiences. Positive placement experiences have been shown to improve students' attitudes to psychiatry (Eagles et al 2007) and positive attitudes of teachers at medical school can be influential in helping students choose psychiatry as a career (McParland et al 2003;Dein et al 2007). Despite these positive influences, psychiatry is often viewed as a lower status specialty among both students and professionals (Hunt et al 1996;Eagles et al 2007) and is seen by students as an unattractive career choice about which they often hold misconceptions (Rajagopal 2004).…”
Section: Introductionmentioning
confidence: 99%